Analisis Framing Pemberitaan Putusan Mahkamah Konstitusi: Studi Pada Berita Syarat Usia Calon Presiden Dan Calon Wakil Presiden Di Mahkamah Konstitusi Tahun 2023 - Fadillah, Muhammad Iqbal; Kalaloi, Abdul Fadli; Alwaton, Yogie (eProceedings of Management, 2024)
The Constitutional Court's decision regarding the age limit for presidential and vice presidential candidates wasratified which resulted in a new decision to remain at a minimum age of 40 years but with the addition of the phrase"or has/is currently holding a position elected through general elections, including regional head elections". Thiscaused many reactions and opinions from the public, including the media, in reporting the decision. This researchaims to determine how the media frames news about the Constitutional Court's decision regarding the age limit forpresidential and vice presidential candidates on the media tempo.co and detik.com. This research uses a constructivistparadigm and qualitative research methods with analytical methods framing Robert N. Entman model. The results ofthis research show that tempo.co frames the news by highlighting critical news by considering the decision as apolitical, legal and nepotism problem. Meanwhile, detik.com framed the news by highlighting the news of theConstitutional Court's decision which considered the decision to be a problem of the lack of opportunities given toyoung people in leadership in Indonesia to become leaders. Keywords-constitutional court decision, Robert N. Entman framing analysis, media Tempo.co and Detik.com